Perceived Influence of Students’ Demographic Variables on Their Access to Financial Aids in Public Universities in Rivers State, Nigeria - Eseyin, Emmanuel Olorunleke (Journal of Education and Research, 2018)
The paper investigated the perceived influence of students’ demographic variables on their access to financial aids in public Universities in Rivers State, Nigeria. Six questions were formulated to guide the study and five hypotheses tested at 0.05 level of significance. The design adopted for the study was an analytical survey. The population of the study included 78, 216 students (34,997 male and 43,219 female) in the three public Universities in Rivers State. The sample of the study covered 791 students (Male= 395 and Female= 396) selected through the random sampling technique while Taro Yamane method of sample size determination was used for determining the sample size. The instruments used for collecting responses from students were questionnaire and a ten items interview schedule. The research questions were answered using frequency, percentage and cumulative percentage. Findings of the study revealed that students’ demographic variables have an influence on their access to financial aids in public Universities in Rivers State, Nigeria. The implication of this is that the government’s expenditure on education will continue to increase in the absence of these alternative financial aids in the public Universities in Rivers State, Nigeria.